2008
DOI: 10.1088/1748-6041/3/4/044106
|View full text |Cite
|
Sign up to set email alerts
|

The anticoagulant ability of ferulic acid and its applications for improving the blood compatibility of silk fibroin

Abstract: The hemocompatibility of silk fibroin (SF) was improved with ferulic acid (FA) by graft polymerization. Ferulic acid is an active ingredient of many Chinese herbal medicines, such as Chuanxiong (Rhizoma ligustici wallichii), Danggui (Angelica sinensis) and Awei (Asafoetida giantfennel), which have been used to treat cardiovascular diseases by Chinese physicians for thousands of years. The inhibitory functions of FA on blood coagulation and erythrocyte agglutination were first characterized by a Lee-White test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…To date, a number of studies have evaluated the hemocompatibility of silk [19-21], silk alloys composed of silk and collagen [22, 23], silk and keratin [24], silk and chitosan [25], silk blends with either heparin [22] or ferulic acid [26], or silk modified chemically through sulfation [27, 28] or grafting with S-carboxymethyl keratin [24] or heparin [25]. We previously determined the impact of processing parameters on the hemocompatibility of pure silk films by using human whole blood and reference materials [29].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of studies have evaluated the hemocompatibility of silk [19-21], silk alloys composed of silk and collagen [22, 23], silk and keratin [24], silk and chitosan [25], silk blends with either heparin [22] or ferulic acid [26], or silk modified chemically through sulfation [27, 28] or grafting with S-carboxymethyl keratin [24] or heparin [25]. We previously determined the impact of processing parameters on the hemocompatibility of pure silk films by using human whole blood and reference materials [29].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies reported rapid blood coagulation when exposed to soluble silk fibroin and silk-collagen scaffolds [14,15] and reduced clotting for functionalised silk substrates for example silk blends with either heparin, ferulic acid or chemical modification of silk such as sulphation or grafting of S-carboxymethyl keratin [1417]. Qualitative methods suggested higher serum protein adsorption and fibrin polymerisation for silk fibres when compared to methanol treated silk films [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Ferulic acid have also been used to improve haemostatics during silk weaving. 8,9 Phenolic acids which includes about half a dozen chemicals in Ferula spp. possess emotional improving and antidepressant activities.…”
Section: Discussionmentioning
confidence: 99%